IDENTIFIKASI NEMATODA USUS SOIL TRANSMITTED HELMINTH (STH) DENGAN METODE RITCHIE PADA ANAK DESA BAJO INDAH KABUPATEN KONAWE - Sarkian Salsabila, Waode Ery; Idris, Sri Aprilianti; Balaka, Kemal Idris (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2024)
Intestinal worm infection is a disease caused by the entry of intestinal worms into the human body. This infection is caused by soil-transmitted helminths (STH). Indonesia is a tropical country with high humidity and has a good environment for worm breeding, especially Soil Transmitted Helminths (STH). Worm infections pose a risk to children, especially groups who occupy elementary schools. One of the causes of the risk of worms to children is soil. The purpose of this study was to determine the morphology and species of Intestinal Nematode Worm Eggs (STH) in Children using the Formol-ether Sedimentation method. This type of research is descriptive, namely to see the description and identify the results of the formalin and ether sedimentation methods. The samples used were 22 samples of feces. The results of the study on 22 samples of feces of children from Bajo Indah Village were 4 positive samples contained intestinal nematode eggs, namely Trichuris trichura, while 18 samples were negative. .